An Ecological Basis for Dual Genetic Code Expansion in Marine Deltaproteobacteria - Kivenson, Veronika; Paul, Blair G.; Valentine, David L. (Frontiers in Microbiology, 2021)
Marine benthic environments may be shaped by anthropogenic and other localized events, leading to changes in microbial community composition evident decades after a disturbance. Marine sediments in particular harbor exceptional taxonomic diversity and can shed light on distinctive evolutionary strategies. Genetic code expansion is a strategy that increases the structural and functional diversity of proteins in cells, by repurposing stop codons to encode noncanonical amino acids: pyrrolysine (Pyl) and selenocysteine (Sec). Here, we report both a study of the microbiome at a deep sea industrial waste dumpsite and an unanticipated discovery of codon reassignment in its most abundant member, with potential ramifications for interpreting microbial interactions with ocean-dumped wastes. The genomes of abundant Deltaproteobacteria from the sediments of a deep-ocean chemical waste dump site have undergone genetic code expansion. Pyl and Sec in these organisms appear to augment trimethylamine (TMA) and one-carbon metabolism, representing an increased metabolic versatility. The inferred metabolism of these sulfate-reducing bacteria places them in competition with methylotrophic methanogens for TMA, a contention further supported by earlier isotope tracer studies and reanalysis of metatranscriptomic studies. A survey of genomic data further reveals a broad geographic distribution of a niche group of similarly specialized Deltaproteobacteria including at sulfidic sites in the Atlantic Ocean, Gulf of Mexico, Guayamas Basin, and North Sea, as well as in terrestrial and estuarine environments. These findings reveal an important biogeochemical role for specialized Deltaproteobacteria at the interface of the carbon, nitrogen and sulfur cycles, with their niche adaptation and ecological success potentially augmented by genetic code expansion.